AUGMENTED REALITY REVOLUTIONIZING LANGUAGE SERVICES: AN IN-DEPTH EXPLORATION - Bezzaoucha, Ilhem (University of Darussalam Gontor, 2024)
The rapid evolution of technology is reshaping the landscape of interpreting, with augmented reality(AR) emerging as a potent force driving transformative changes. This paper meticulously exploresthe profound implications of AR on interpreting practices, aiming to elucidate its transformativepotential and influence on the future trajectory of the profession. Through an exhaustive examinationof AR technology, current interpreting trends, and envisioned applications of AR in languageservices, this paper offers a comprehensive understanding of its impact on the interpreting domain.AR represents a paradigm shift in interpreting practices, offering unprecedented opportunities forlanguage professionals to enhance communication and comprehension in multilingual contexts.Unlike virtual reality (VR), which immerses users in entirely synthetic environments, AR overlaysdigital information onto the physical world, thereby enriching real-world experiences. This papercritically examines current interpreting trends, including the integration of AR into interpretationworkflows, and delves into ethical considerations arising from the use of AR in interpreting. Byaddressing issues related to privacy, accuracy, and the impact on human interpreters' roles, this paperemphasizes the importance of responsible and ethical use of technology in language services.